2016
DOI: 10.1123/jmld.2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Motor Skill Retention Is Modulated by Strategy Choice During Self-Controlled Knowledge of Results Schedules

Abstract: Investigations into the strategies that are used by participants when they control their knowledge of results (KR) schedule during practice have predominantly relied on multiple-choice questionnaires. More recently, open-ended questions have been used to allow participants to produce their own descriptions rather than selecting a strategy from a predetermined list. This approach has in fact generated new information about the cognitive strategies used by learners to request KR during practice (e.g., Laughlin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
2
16
0
3
Order By: Relevance
“…At the end of skill acquisition described in Phase One, participants were asked to complete a pen and paper questionnaire regarding their practice experience. The questions ( Table 1 ) were based on questionnaires employed in previous studies ( Laughlin et al, 2015 ; Carter et al, 2016 ).…”
Section: Phase Twomentioning
confidence: 99%
See 2 more Smart Citations
“…At the end of skill acquisition described in Phase One, participants were asked to complete a pen and paper questionnaire regarding their practice experience. The questions ( Table 1 ) were based on questionnaires employed in previous studies ( Laughlin et al, 2015 ; Carter et al, 2016 ).…”
Section: Phase Twomentioning
confidence: 99%
“…Effect sizes for these analyses are represented by Cramer’s V , whose value increases from 0 to 1 with the strength of association between two variables. Next, following the analyses employed by Carter et al (2016) we conducted Mann–Whitney U tests for each retention test and views in each half of skill acquisition to compare the dominant Performance view to All other views of haptic assistance. As before, we opted for exact calculations and determined effect sizes as r , the ratio of the z -score to the square root of the total sample size on which the test-statistic was based ( Field, 2009 ).…”
Section: Phase Twomentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, when experimenter-controlled feedback is provided after relatively good trials, it has resulted in more effective performance in retention tests than when it is provided after relatively poor trials (e.g., Chiviacowsky & Wulf, 2007;Chiviacowsky, Wulf, Wally, & Borges, 2009). Whilst such findings have been argued to suggest an important role for motivation in skill learning (Lewthwaite & Wulf, 2010), researchers have recently shown that the strategies for requesting KR may vary as a function of the number of practice trials completed (e.g., Carter & Patterson, 2012;Carter, Rathwell, & Ste-Marie, 2016), with KR being requested only after relatively good trials later in practice. Moreover, researchers have also shown that awareness of KR content (i.e., whether KR is given after the three best or three worst trials) results in superior learning, irrespective of whether the KR reflects good or poor trials (Patterson & Azizieh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some researchers have argued that having choice or control is intrinsically rewarding and satisfies the basic psychological needs of autonomy and/or competence, which in turn enhances motor learning (Chiviacowsky, 2014;Lewthwaite, Chiviacowsky, Drews, & Wulf, 2015;. On the other hand, the learning advantages have been suggested to be predominantly driven by the learner's ability to engage in performance-dependent strategies (e.g., error estimation) that serve to reduce the uncertainty regarding task performance (Carter, Carlsen, & Ste-Marie, 2014;Carter, Rathwell, & Ste-Marie, 2016;Chiviacowsky & Wulf, 2005;Grand et al, 2015;Hansen, Pfeiffer, & Patterson, 2011;Huang, Shadmehr, & Diedrichsen, 2008). These explanations are often referred to as the motivational-influences perspective and the information-processing perspective, respectively (see both Carter et al, 2014, andSanli et al, 2013).…”
mentioning
confidence: 99%